Dynamic response analysis of monopile-supported offshore wind turbine on sandy ground under seismic and environmental loads - He, Wentao; Takahashi, Akihiro (Soil dynamics and earthquake engineering (1984), 2025)
Monopiles are the most widely adopted foundation type for Offshore Wind Turbines (OWTs) in shallow waters. With the expansion of the construction of OWT, the number of OWT farms in seismic regions increases globally including the coastal areas of Japan and China. It is necessary to evaluate the impact of earthquakes including the vibration and soil liquefaction on the OWTs supported by the monopile foundation, while the effects of liquefaction on offshore structures, especially for OWTs with monopiles, have not been sufficiently studied. This study investigates the seismic response of the monopile-supported OWTs with the use of an advanced soil model. A three-dimensional numerical model is built, and dynamic analyses are carried out using the OpenSees framework. The pressure-dependent multi-yield (PDMY03) constitutive model is used to simulate the dynamic soil behavior. The applicability of the large-diameter pile modeling method for proper soil-pile interaction modeling in this numerical analysis is first validated through centrifuge tests on monopiles subjected to lateral loading. The dynamic analyses are then carried out to demonstrate the seismic response of the entire OWT system. The numerical results indicate that the contribution of higher modes of vibration is becoming of increased importance for large wind turbines and soil-structure interaction plays a significant role in the dynamic response. Moreover, the monopile-supported OWT in dense sand deposits experiences substantial lateral displacement and rotation under the combined action of wind and earthquake loads when liquefaction occurs. •Seismic response of offshore wind turbines on monopile is analyzed by 3D FE analysis.•Modeling is validated through the simulation of laterally loaded monopiles.•Impacts of liquefaction and wind load on the monopile response are demonstrated.